Dieulafoy disease of the trachea with recurrent episodes of massive hemoptysis: A case report. Issue 5 (February 2017) - Yang, Danrong; Rong, Chaohui; Gu, Jie; Xu, Ling; Zhang, Jiayin; Zhang, Guobin; Shen, Ce
Abstract: Rationale: Dieulafoy disease is characterized by the presence of dilated, tortuous arteries that project into the submucosa of the gastrointestinal tract and less frequently the bronchus. Patient concerns: Dieulafoy disease of the trachea has not been previously described. A 60-year-old woman with recurrent episodes of massive hemoptysis. Diagnoses: Dieulafoy disease of the trachea. Interventions: :Selective arterial embolization was undertaken. Outcomes: The intervention was successful and no fresh episode of acute hemoptysis was observed. Lessons: Apart from the bronchus, vascular anomaly may also be present in the trachea in Dieulafoy disease.